The specificity of psychotherapeutic competence: A study protocol on the development of facilitative interpersonal skills across professional pathways - Niccolò Fiorentino Polipo; Constanze Maria Springinsfeld; Nina Pfatrisch; Amelie Bihl; Gabor Aranyi; Andrea Jesser (PLoS ONE, 2026)
Introduction Facilitative interpersonal skills (FIS) are widely used as an operationalization of therapists’ interpersonal competence. However, the degree to which FIS are specific outcomes of formal psychotherapy training or instead reflect more general abilities developed across different professional pathways or outside of any formal training is unclear. Methods and analysis To test whether psychotherapy students show a stronger stage-related increase in FIS levels than students from other fields, this study protocol outlines a cross-sectional cohort design in which FIS levels are assessed at three training stages (entry university level, end of bachelor, end of master) across four professional pathways. The group comparisons include (1) psychotherapy students as the reference group, (2) nursing and (3) teacher education students as comparison groups with high interpersonal demands but without mental health training, and (4) students from the disciplines of Science, Technology, Engineering, and Mathematics (STEM) as a baseline group with low interpersonal demands and no mental health training. We will use linear mixed-effects models with professional pathway and training stage as fixed effects. The primary test will evaluate the fixed effects of the factors professional pathway and training stage, and their interaction. Ethics and dissemination Compared to previous studies, our non-clinical, non-interventionist design eliminates any risk of harm to patients and removes variance associated with patient and dyadic factors. Approval has been obtained from the Ethics Commission at Sigmund Freud Private University Vienna. Data and analysis scripts will be shared via open-access repositories. We intend to disseminate results through at least three peer-reviewed publications: primary analyses, secondary analyses, and a theoretical synthesis on implications for psychotherapy training and interprofessional competence.